Success Factors For Managing Benchmarking Process - Deou, Seang Sin (1998)
This study intends to investigate the extent of benchmarking practices and the success factors for benchmarking process by electrical and electronics companies in Penang. Data collection method was through the use of mail questionnaires that were administered through personal contacts for all the companies selected. The result indicated that the electrical and electronics companies in Penang are increasingly making use of benchmarking, a trend expected to continue for the next five years. Most of the companies are still in the early stage of practising benchmarking.